Gender Differences in Individual Dishonesty Profiles - Muñoz García, Adrián; Gil-Gómez de Liaño, Beatriz; Pascual-Ezama, David (Frontiers in Psychology, 2021)
Dishonesty has an enormous impact on any facet of our society. It can cause even billions of annual losses in workplaces, so the efforts to understand dishonest behavior have grown nowadays. However, one of the main questions yet to be answered is whether there might be gender differences in dishonesty: Do men behave more dishonestly than women? Although the literature points towards a positive answer to that question, there is still no clear consensus about it. In the current work, we studied gender differences in dishonesty in a large sample (2452 participants) using a new paradigm recently developed by Pascual-Ezama et al. (2020) based on a variation of the classic "Die-under-the-cup" task. This new paradigm allows us to individually identify different dishonesty profiles and look for gender differences among them. Results show that men are more prone to behave dishonestly than women with small rewards, who seem satisfied without maximizing the potential reward. However, differences disappear when there is no reward. Men show more "radical" dishonest behavior than women too. The results provide novel insights showing that gender differences might be shaped by diverse factors rather than just differences associated with gender.